Environmental impacts of urban growth and land use changes in tropical cities - Ogunbode, Timothy O.; Oyebamiji, Victor O.; Sanni, David O.; Akinwale, Emmanuel O.; Akinluyi, Francis O. (Frontiers in Sustainable Cities, 2025)
Urban centers across the globe are undergoing rapid land use changes due to population growth, economic development, and urbanization. These changes have a profound impact on environmental dynamics and urban livelihoods. This study investigates land use changes and their environmental implications on urban livelihoods in Iwo, Nigeria. The research explores the patterns and drivers of land use changes over the past four decades and evaluates their effects on environmental quality and urban livelihoods. A combination of remote sensing and survey methods was employed. Landsat images from 1982 to 2023 were analyzed using supervised classification techniques to map changes in land cover categories such as built-up areas, vegetation, farmland, bare land, and water bodies. Additionally, a survey was conducted with 550 residents, selected through simple random sampling, to identify the key drivers of urban expansion from the residents’ perspectives. Descriptive analysis revealed that most respondents had lived in Iwo for over 30 years, with many engaged in farming, trading, and civil service. Factor analysis was used to identify significant variables driving urban growth. The results indicate a substantial increase in built-up areas, from 9.30 km2 in 1982 to 30.69 km2 in 2023, alongside a significant decrease in vegetation cover. Farmland area showed an increasing trend, while bare land decreased. Key drivers of urban growth identified include religious activities, availability of land resources, small-scale businesses, government initiatives, and educational institutions. The environmental implications include deforestation, reduced green spaces, increased surface runoff, and pollution, which affect air quality, water resources, and biodiversity. This study highlights the importance of sustainable urban planning to balance growth with environmental preservation and social equity. The implementation of green infrastructure, effective waste management, and comprehensive urban planning policies is crucial to enhancing resilience and quality of life in Iwo.